[Right ; left ; Center] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Interview with Greg Honasan about the Rightist movement in military ; the left wing rebels, the Communist Movement in Quezon Province, AFP spokesmen on their offering to opposite ends of political spectrum and with other people, like the political analysts.
Right (14 min.) -- Left (18 min.) -- Center (23 min.)
VHS.
Keywords: Honasan, Gregorio -- Interviews; Reform the Armed Forces Movement; New People's Army; Civil-military relations -- Philippines; Communists -- Interviews; Counterinsurgency -- Philippines; Left-wing extremists -- Philippines; Philippines -- Social conditions